1998
DOI: 10.1016/s0022-5347(01)63698-x
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Determination of Chemical Composition of Urinary Calculi by Spiral Computerized Tomography

Abstract: This study demonstrates that the chemical composition of urinary calculi can be accurately determined by CT scanning in an in vitro setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(82 citation statements)
references
References 17 publications
5
75
1
1
Order By: Relevance
“…More recently, Mostafavi et al [18] reported that the best single CT parameter for assessing the chemical composition of stones was the absolute CT-attenuation value at 120 kV rather than at 80 kV, a result that is not confirmed by our data. They demonstrated in an in vitro setting that the absolute CT-attenuation value at 120 kV was able to identify uric acid, struvite and calcium oxalate stones but was unable to distinguish between calcium oxalate and brushite stones and struvite and cystine stones.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…More recently, Mostafavi et al [18] reported that the best single CT parameter for assessing the chemical composition of stones was the absolute CT-attenuation value at 120 kV rather than at 80 kV, a result that is not confirmed by our data. They demonstrated in an in vitro setting that the absolute CT-attenuation value at 120 kV was able to identify uric acid, struvite and calcium oxalate stones but was unable to distinguish between calcium oxalate and brushite stones and struvite and cystine stones.…”
Section: Discussioncontrasting
confidence: 95%
“…However, cystine and uric acid stones were identified in one study [13], but not in another [12]. Mostafavi et al [18] were able to determine accurately at dual kilovoltage the chemical composition of urinary tract calculi by scanning the whole urinary tract with 1-mm collimation and a pitch of 1:1, which is impractical in daily practice. More recently, it was shown in vitro that visualization of stone structure was greatly enhanced using bone windows and a narrow slice width [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown that a certain prediction of the chemical composition can be made by analyzing the CT attenuation of the calculus if the CT system is well calibrated [9][10][11]. However, despite promising in vitro results, the reproducibility of the results in vivo has not been found satisfactory [11].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that the density of opacified calyces should be uniformly more than 150 HU but less than 250 HU because published CT measured calculus densities have varied between 250-1,600 Hounsfield units (HU) [3][4][5][6][7][8], and unpublished data from our department have shown that the renal parenchyma measures around 100 HU in the excretory phase. Initial studies of CT pyelography using slightly different techniques [9,10] have been promising, and in this retrospective study we critically analyze the reproducibility of CT pyelography in routine use.…”
Section: Introductionmentioning
confidence: 99%